Tax counseling and assistance in implementing an E-KTP-based service queue system in Randubango Village, Mojokerto - Syamsudduha Syahrorini; Shazana Dhiya Ayuni; Akhmad Mulyadi; Izza Rosidah; Fatahillah Ikra Negara (Universitas Muhammadiyah Magelang, 2023)
Taxation stands as a potential income factor, significantly contributing to regional revenue. The objective of community service in Randubango Village, Mojokerto, is to elevate public awareness of tax payments and foster innovation in the queuing system for administrative services. The implementation of this community service unfolds in three stages: licensing, awareness-raising counseling, and assistance in deploying the queuing system for administrative services, integrating KTP scanning and monitoring. The outcome of this program manifests in an increased awareness of the importance of tax payments and the improved operation of the administrative services queue system.